The Effect of Acceptance and Commitment Therapy on Improvement of Quality of life in Patients with Multiple Sclerosis - mohammad Barooti; Ali Akbar Soliemanian; Ali Mohamadzadeh Ebrahimi (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: Multiple Sclerosis (MS) is a chronic disease of the central nervous system, which its physical symptoms and psychological consequences lead to a decrease in the quality of life in the affected population. The purpose of this study was to investigate the effect of acceptance and commitment therapy (ACT) on improving the quality of life of patients with Multiple Sclerosis. Methods: The research method was semi-experimental and its design was a pretest-posttest with the control group. The statistical population consisted of all patients of members shirvan city multiple sclerosis association (N=50) in 2017. The sample consisted of 26 volunteers who were randomly assigned to two experimental and control groups (for each group 10 subject). Data gathering instrument was Multiple Sclerosis Quality of Life-54 (MSQOL-54) questionnaire that completed by every two groups in before and after the intervention. Experiment group participated in 8 sessions of ACT and the control group did not receive any intervention. Covariance analysis method was used to analyze the data. All analyzes were performed using SPSS-24 Results: The findings showed that ACT had a significant effect on improving the quality of life and dimensions of physical and mental health in the experimental group (p<0.001). Conclusion: The results showed that ACT improved the quality of life in MS patients; therefore, it is suggested that, besides medical treatments, ACT is used to improve the quality of life of patients with MS.